Black holes and cosmic censorship - Düztaş, Koray. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2014)
This thesis starts with a brief review of causality conditions, gravitational collapse and singularity theorems. Cosmic censorship conjecture is introduced and the need for such a conjecture to preserve the deterministic nature of physics is explained. Examples of thought experiments which are designed to test the validity of cosmic censorship conjecture, are given. These examples involving cases of both particles and fields, are considered to have conceptual importance. Spinor algebra and analysis is reviewed. Newman-Penrose formalism is introduced. The derivations of Teukolsky’s solutions for test fields in Kerr space-time are given. Using these solutions an original thought experiment involving an extremal Kerr black hole and a test electromagnetic is constructed. It is shown that cosmic censorship conjecture is not violated in this case. The examples of thought experiments with particles that start with nearly extremal black holes instead of extremal ones are given. Another original thought experiment is constructed using integer-spin test fields and a nearly extremal Kerr black hole. It is found that cosmic censorship conjecture is violated in this case as long as radiative and self-force effects are ignored. Finally the case of neutrino fields are considered as an example of half integer-spin. It is shown that neutrino fields lead to a generic violation of the conjecture which is unique among all the attempts since the conjecture was introduced.
Keywords: Black holes (Astronomy); Relativity (Physics)